The coming wave technology, power, and the Twenty-first Century's greatest dilemma - Suleyman, Mustafa (Crown, 2023)
A stark and urgent warning on the unprecedented risks that a wave of fast-developing technologies poses to global order, and how we might contain them while we have the chance-from a cofounder of the pioneering AI company DeepMind. Imagine a world in which anyone with a $20,000 desktop DNA synthesizer could develop and unleash a deadly virus. Imagine an undetectable deepfake video of a U.S. president making a racial slur racing across the internet on the eve of an election. Imagine terrorists or paramilitaries stockpiling autonomous weapons designed to make their own decisions about when to engage. As cofounder of DeepMind, the pioneering AI company now owned by Google, Mustafa Suleyman has witnessed firsthand just how rapidly our technology is advancing-and how flawed our approaches to grappling with these changes are. The coming decades, he argues, will be defined by a burst of innovation, an inevitable wave of powerful, fast-proliferating new technologies across fields like synthetic biology, artificial intelligence, and quantum computing. Driven forward by immense strategic and financial incentives, these breakthroughs will solve huge challenges and create vast wealth-but upheaval, too, on a once unimaginable scale. Will humankind make it through the narrow corridor between dystopia and catastrophe? In The Coming Wave, Suleyman shows how this new technological super-wave fits a historical pattern of innovation and proliferation, while departing from it in key ways: namely, the speed of change, the breadth of risks, and the wave's potential to democratize access to dangerous, world-altering power. The cumulative risks threaten the very nation state, humanity's centuries' old "grand bargain" of living under centralized authority in exchange for security. As our fragile governments sleepwalk into catastrophe, humanity is left in an existential bind, with techno-authoritarianism on one side and even more catastrophic outcomes, like societal collapse, on the other. We are about to cross a critical threshold in the history of our species. In this groundbreaking book from the ultimate AI insider, Suleyman firmly establishes "the containment problem"-or the challenge of maintaining human control over dangerous technologies-as the essential dilemma of our age, showing that radical steps must be taken if we are to live alongside technology of once unimaginable power"--Provided by publisher.